2019
DOI: 10.3390/ijms20030549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichoderma velutinum and Rhizoctonia solani on the Metabolome of Bean Plants (Phaseolus vulgaris L.)

Abstract: The common bean (Phaseolus vulgaris L.) is one of the most important food legume crops worldwide that is affected by phytopathogenic fungi such as Rhizoctonia solani. Biological control represents an effective alternative method for the use of conventional synthetic chemical pesticides for crop protection. Trichoderma spp. have been successfully used in agriculture both to control fungal diseases and to promote plant growth. The response of the plant to the invasion of fungi activates defensive resistance resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 42 publications
5
24
0
Order By: Relevance
“…In addition, the detailed metabolome and transcriptome analysis have shown that T. harzianum colonization strongly affects and remodels phenylpropanoid pathway of tomato plants [48]. Our data on decreased NBI in Trichoderma treated tomato plants of cultivar Gružanski zlatni indicates a shift from primary to secondary metabolism, and in accordance with previously cited papers, better resistance to diseases or insects might be expected [47,48].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the detailed metabolome and transcriptome analysis have shown that T. harzianum colonization strongly affects and remodels phenylpropanoid pathway of tomato plants [48]. Our data on decreased NBI in Trichoderma treated tomato plants of cultivar Gružanski zlatni indicates a shift from primary to secondary metabolism, and in accordance with previously cited papers, better resistance to diseases or insects might be expected [47,48].…”
Section: Discussionsupporting
confidence: 91%
“…The increase of total flavonoids and total polyphenols was also observed in leaves from 7 days up to 60 days after Trichoderma foliar application [14]. Moreover, six flavonoids that were significantly increased in bean plants in the presence of Trichoderma strain with major stimulation of plant growth have been identified [47]. In addition, the detailed metabolome and transcriptome analysis have shown that T. harzianum colonization strongly affects and remodels phenylpropanoid pathway of tomato plants [48].…”
Section: Discussionmentioning
confidence: 90%
“…The untargeted analysis of olive leaf metabolome allowed the evaluation of significant differences between plants treated with the different Trichoderma strains or metabolites. This approach has been used in other studies on different plants and with different techniques [ 79 , 80 ]. Previous studies on olive leaves revealed differences in individual and total phenolic content depending upon both the season and the cultivar [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large set of potentially bioactive strains was identified in this study. Strains able to significantly interfere with pathogen development also transiently affected plant growth, suggesting that a complex set of molecules is produced during the tripartite interaction (Mayo-Prieto et al, 2019). Our future goal will be to identify the determinants of these specific interactions occurring among the BCA, the fungus, and the host, as detailed knowledge of their interaction is essential for developing novel plant protection strategies (Berendsen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%